Lythrum salicaria L. Extracts Down-Regulate Pro-Inflammatory Cytokine Release and Inhibit the Bacterial Triggers of Some Autoimmune Inflammatory Diseases - Puisais, Audric; Cock, Ian Edwin (Pharmacognosy Communications)
Background: Lythrum salicaria L. has been used traditionally to treat a variety of conditions including bacterial infections and inflammation. Despite this, only preliminary studies have examined L. salicaria extracts for therapeutic properties relevant to these traditional uses. Materials and Methods: Dried L. salicaria whole plant material was extracted with solvents of various polarities and tested for the ability to modulate the release of IFN-γ, IL-6 and TNF-α from RAW 264.7 cells using a BD™ cytometric bead array assay. The ability of the extracts to inhibit the growth of some bacterial triggers of selected autoimmune inflammatory diseases was also quantified by disc diffusion and liquid dilution MIC assays. The ΣFIC of extract/antibiotic combinations was determined and used to classify the class of interaction. Toxicity was evaluated using Artemia nauplii and HDF cytotoxicity assays. Results: Methanolic and aqueous L. salicaria extracts substantially reduced the release of IFN-γ, IL-6 and TNF-α from RAW 264.7 cells in both PMA/ionomycin and LPS stimulatory models. Additionally, the methanolic, aqueous and ethyl acetate extracts strongly inhibited the growth of several bacterial triggers of autoimmune diseases, with MIC values as low as 240 μg/mL against some bacteria. Furthermore, combining the extracts with conventional antibiotics resulted in significant potentiation of the inhibitory activity for some combinations, with two synergistic and 19 additive combinations detected. Notably, three antagonistic combinations were also noted. None of the individual components (nor the combinations) were toxic in the ALA or MTS assays. Conclusion: Lythrum salicaria extracts down-regulate the release of IFN-γ, IL-6 and TNF-α from RAW 264.7 cells and inhibit the growth of bacterial triggers of rheumatoid arthritis, ankylosing spondylitis, multiple sclerosis and rheumatic fever. Further in vivo testing and studies to determine the anti-inflammatory and antibacterial mechanisms and to identify the bioactive principles in the L. salicaria extracts is warranted
Keywords: Medicinal Plants; Immunomodulation; Pro-Inflammatory Cytokines; Synergy; Rheumatoid Arthritis; Ankylosing Spondylitis; Multiple Sclerosis; Antibacterial Activity.